New Fractional Dynamic Inequalities via Conformable Delta Derivative on Arbitrary Time Scales - Ahmed A. El-Deeb (MDPI AG, 2021)
Building on the work of Josip Pečarić in 2013 and 1982 and on the work of Srivastava in 2017. We prove some new <semantics>α</semantics>-conformable dynamic inequalities of Steffensen-type on time scales. In the case when <semantics>α=1</semantics>, we obtain some well-known time scale inequalities due to Steffensen inequalities. For some specific time scales, we further show some relevant inequalities as special cases: <semantics>α</semantics>-conformable integral inequalities and <semantics>α</semantics>-conformable discrete inequalities. Symmetry plays an essential role in determining the correct methods to solve dynamic inequalities.